A critical review of forced convection in microchannels - Kadhim, Ghufran; Al-Saadi, Ahmed (Al-Qadisiyah journal for engineering science, 2025)
The dissipation of excessive heat flux is presently a significant issue that needs to be addressed due to the use of microdevices in fields such as nuclear energy, electronic devices, aerospace engineering, building engineering, and more. Because of their increased heat transfer and compact size, microchannel cooling systems have become an effective way to manage the temperature of microdevices and equipment upgrades. However, due to the increasing demands placed on microdevices for thermal load, controlling the temperature, and conserving energy, efficient heat exchangers, in particular microchannels, are attracting a growing amount of interest. A key passive technique for successfully increasing the heat transfer of the microchannel cooling system and improving the performance of microchannels is channel shape optimization. Therefore, the characteristics of microchannel geometry from prior research have been reviewed, categorized, and summed up in this article. The analysis focuses primarily on structural features and microchannel geometry attributes that enhance the impact of pressure drop and heat transfer. It also presents the relationship between boiling heat transfer and the geometrical features of microchannel flow and discusses the potential study directions for microchannel geometry design. The current review of microchannels will provide researchers working on these microchannel components with specialized expertise. In an effort to improve the impact of heat transfer, this study reviews, categorizes, and summarizes the characteristics of prior studies' microchannel geometry.